Influence of ground pumice powder on the bond behavior of reinforcement and mechanical properties of self-compacting mortars - Benli, Ahmet; Karatas, Mehmet; Sastim, M. Veysel (Techno-Press, 2017)
The aim of this study is to investigate the effect of the bond strength of self-compacting mortars (SCMS) produced from ground pumice powder (GPP) as a mineral additive. In this scope, six series of mortars including control mix were prepared that consist of 7%, 12%, 17%, 22% and 27% of ground pumice powder by weight of cement. A total of 54 specimens of 40x40x160 mm were produced and cured at the age of 3, 28 and 90-day for compressive and tensile strength tests and 18 specimens of 150x150x150 mm mortar were prepared and cured at 28 days for bond strength tests. Flexural tensile strength and compressive strength of 40x40x160 mm specimens were measured at the curing age of 7, 28 and 90-day. Mini V-funnel flow time and mini slump flow diameter tests were also conducted to obtain rheological properties. As a result of the study, it was observed that the SCMs containing 12% of GPP has the highest bond strength as compared to control and GPP mortars. Compressive strength slightly increased up to 12% of GPP.
Keywords: self-compacting mortar; ground pumice powder; bond strength; fresh properties; mechanical properties